Four DOF Robot Manipulator Control Using Feedback Linearization Based on Sliding Mode Control - Alqaisi, Walid Kh.; Soliman, Mostafa; Badawi, Ahmed; Elzein, I. M.; El-Bayeh, Claude Ziad (Association for Scientific Computing Electronics and Engineering (ASCEE), 2025)
This paper investigates the performance of a four-degree-of-freedom (4DOF) robot arm using feedback linearization based on sliding mode control (FLSM). FLSM simplifies complex nonlinear control solutions and mitigates the effects of the highly coupled dynamic behavior of the 4DOF manipulator. The controller takes into account uncertain dynamics and unexpected disturbances such as changes in payload, variations in wind, and gravity effects in different directions. The stability of the proposed controller is achieved using the manipulator model and FLSM without linearizing the model. Stability is analyzed using a Lyapunov function, and MATLAB Simulink is utilized to simulate the real parameters of the Quanser QArm. The results are compared with those obtained using a PID controller.